Pharmacovigilance Practices by Healthcare Providers in Oncology: A Cross-Sectional Study - Hadeel Alkofide; Haya M. Almalag; Mashael Alromaih; Lama Alotaibi; Njoud Altuwaijri; Noha Al Aloola; Jawza F. Alsabhan; Ghada A. Bawazeer; Lobna Al Juffali; Rihaf Alfaraj; Nora Alkhudair; Raniah Aljadeed; et al. (MDPI AG, 2024)
Investigating pharmacovigilance (PV) practices among oncology healthcare providers (HCPs) is crucial for patient safety in oncology settings. This study aimed to assess the awareness, attitudes, and practices towards PV and identify barriers to effective adverse drug reaction (ADR) reporting for HCPs working in oncology-related settings. Employing a cross-sectional survey design, we collected data from 65 HCPs, focusing on their experiences with ADR reporting, education on ADR management, and familiarity with PV protocols. The results showed that about half of the responders were pharmacists. Around 58.9% of the respondents reported ADRs internally, and 76.9% had received some form of ADR-related education. However, only 38.5% were aware of formal ADR review procedures. Methotrexate and paclitaxel emerged as the drugs most frequently associated with ADRs. The complexity of cancer treatments was among the common reasons for the low reporting of ADRs by the study participants. The findings highlight the need for enhanced PV education and standardized reporting mechanisms to improve oncology care. We conclude that reinforcing PV training and streamlining ADR-reporting processes are critical to optimizing patient outcomes and safety in oncology, advocating for targeted educational interventions and the development of unified PV guidelines.